2002
DOI: 10.1023/a:1019894008885
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The cationic sphingosine/EPC/DNA complexes form weakly compacted structure, potentially labile in vivo, which might be useful for in vivo gene transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Although any cationic agent would be expected to exhibit some toxicity, especially at high concentrations, previous reports have shown that sphingosine forms complexes with DNA and can facilitate transfection. 33 36 Considering that sphingosine is a natural degradation product of ceramide that is present in all mammalian cells, 37 , 38 it would be expected that this single-tailed cationic amphiphile might be well-tolerated. Accordingly, we substituted sphingosine for DOTAP in the formulations, and monitored the effect of +/– charge ratio on transfection and toxicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although any cationic agent would be expected to exhibit some toxicity, especially at high concentrations, previous reports have shown that sphingosine forms complexes with DNA and can facilitate transfection. 33 36 Considering that sphingosine is a natural degradation product of ceramide that is present in all mammalian cells, 37 , 38 it would be expected that this single-tailed cationic amphiphile might be well-tolerated. Accordingly, we substituted sphingosine for DOTAP in the formulations, and monitored the effect of +/– charge ratio on transfection and toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the well-known toxicity associated with cationic agents, we investigated the potential to utilize sphingosine, a naturally occurring cationic amphiphile that has been shown to bind DNA and facilitate transfection. 33 36 Because sphingosine is generated in lysosomes as a breakdown product of ceramide, cells have mechanisms for degrading/eliminating this molecule, thereby minimizing its toxic effects. 37 , 38 Addition of free, DMSO-solubilized sphingosine to cells is known to activate cathepsin D and trigger apoptosis, but this activation is not observed when sphingosine is incorporated into bilayers.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown in other works that the charge ratio between cationic liposomes and plasmid DNA strongly affects the size, zeta potential, stability, toxicity, and therefore the transfection efficiency of the lipoplexes [ 35 , 36 , 37 ]. Figure 16 presents the transfection efficiency of cosol_MCLs–pFAR4-luc complexes with different PEG lengths at a charge ratio of 8 or 10.…”
Section: Resultsmentioning
confidence: 99%